A Nantucket wedding : a novel - Thayer, Nancy, 1943- (New York : Ballantine Books, 2018)
"Wedding bells are ringing, a family is reunited, and new love is blooming--for better or worse--in this captivating novel from the New York Times bestselling author of The Island House and Secrets in Summer. A few years after losing her beloved husband, Alison is doing something she never thought she would do again: getting married. While placing the finishing touches on her summer nuptials, Alison is anxious to introduce her fiance, David, to her grown daughters: Felicity, a worried married mother of two, and Jane, also married but focused on her career. The sisters have a somewhat distant relationship and Alison hopes that the wedding and the weeks leading up to the ceremony will give the siblings a chance to reconnect, as well as meet and get to know David's grown children. As the summer progresses, it is anything but smooth sailing. Felicity stumbles upon a terrible secret that could shatter her carefully cultivated world. Jane finds herself under the spell of her soon-to-be stepbrother, Ethan, who is as charming as he is mysterious. And even Alison is surprised (and slightly alarmed) by her new blended family. Revelations, intrigue, resentments--as the Big Day approaches, will the promise of bliss be a bust? Against the gorgeous backdrop of the sunswept island of Nantucket, Nancy Thayer sets the stage for a walk down the aisle no one will ever forget"--
"Wedding bells are ringing, a family is reunited, and new romances are blooming--for better or for worse--in an enthralling novel from the New York Times bestselling author of The Island House and Secrets in Summer. It's summer on Nantucket and Alison is finally engaged to the love of her life. Things would be perfect--if only she could make peace between her daughters. Felicity, wild at heart yet a loving mother to her own children, and Jane, the extremely organized and high-earning businesswoman, arrive on the island hoping to get through these next few weeks without ruining their mother's big day. But when Felicity's husband reveals a long-term affair and Jane falls for her soon-to-be step-brother, everyone gets way more drama than they bargained for"--
As she prepares for her long-awaited wedding to David, Alison finds her life thrown into turmoil by family drama involving her grown daughters.
Keywords: Weddings -- Fiction; FICTION / Contemporary Women; FICTION / Sagas; FICTION / Romance / Contemporary; Weddings -- Fiction; Family life -- Fiction; Domestic fiction; Romance fiction